The national parks America's best idea - Duncan, Dayton; Burns, Ken, 1953-; Coyote, Peter; Florentine Films; WETA-TV (Television station : Washington, D.C.); Public Broadcasting Service (U.S.); PBS Home Video; Paramount Home Entertainment (Firm) ([United States] : PBS Home Video ; Hollywood, Calif. : Distributed by Paramount Home Entertainment, 2009)
Traces the birth of the national park idea in the mid-1800s and follows its evolution for nearly 150 years. Using archival photographs, first-person accounts of historical characters, personal memories and analysis from more than 40 interviews, and what Burns believes is the most stunning cinematography in Florentine Films' history, the series chronicles the steady addition of new parks through the stories of the people who helped create them and save them from destruction.
Episode one. The scripture of nature (1851-1890) -- Episode two. The last refuge (1890-1915) -- Episode three. The empire of grandeur (1915-1919) -- Episode four. Going home (1920-1933) -- Episode five. Great nature (1933-1945) -- Episode six. The morning of creation (1946-1980).
DVD; region 1, NTSC; widescreen presentation enhanced for 16x9 televisions; Dolby digital 5.1 surround, 2.0 stereo.
English or dubbed Spanish dialogue with optional English or Spanish subtitles; video description for the visually impaired; closed-captioned.
Narrated by Peter Coyote.
Cinematography, Buddy Squires, Allen Moore, Lincoln Else, Ken Burns ; supervising film editor, Paul Barnes ; episode editors, Paul Barnes, Craig Mellish, Erik Ewers.
Originally broadcast as episodes of the television documentary on PBS in 2009.
Not rated.
Keywords: National parks and reserves -- United States -- History; Nature conservation -- United States -- History; United States. -- National Park Service -- History; Documentary television programs; Historical television programs; Nonfiction television programs; Video recordings for hard of hearing people; Video recordings for people with visual disabilities; DVD-Video.; Geschichte; Nationalpark; USA